Bohemia in London - Brooker, P. author. aut Link
XIII, 210 p. 6 illus.
Keywords: This original study discovers the bourgeois in the modernist and the dissenting style of Bohemia in the new artistic movements of the 1910s. Brooker sees the bohemian as the example of the modern artist, at odds with but defined by the codes of bourgeois society. It renews once more the complexities and radicalism of the modernist challenge.